التزامات البنك الفاتح في الاعتماد المستندي ومسؤوليته القانونية - بن الشيخ, هشام (جامعة الوادي University of Eloued, 2019)
الملخص: يلعب الاعتماد المستندي دوراً مهما للغاية في تسوية عمليات التصدير والاستيراد للبضائع بالنظر لما يوفره من ضمان وتأمين لكل من البائع والمشتري في استيفائهما لحقوقهما المترتبة على عقد البيع الدولي للبضائع وهو ما يدفع قدماً لازدهار التجارة الدولية المرتكزة أساساً على مبدئي السرعة والائتمان. وكغيره من العقود الملزمة لجانبين يرتب عقد الاعتماد المستندي جملة من الالتزامات في ذمة طرفيه المتعاقدين (البنك الفاتح للاعتماد والعميل الآمر)، غير أن خصوصية هذا العقد خاصة في مرحلة التنفيذ تستوجب تحمل البنك لالتزامات أخرى في مواجهة البائع المستفيد من الاعتماد. ولأن البنك يعتبر هو المحور الأساسي للعملية فقد حاولنا من خلال هذه الدراسة تفصيل أهم ما يفرضه عليه (البنك) عقد الاعتماد المستندي من التزامات عقدية تجاه كل من المشتري والبائع ثم ما يقع عليه من مسؤولية قانونية حال أخل بأحد هذه الالتزامات. Abstract: The documentary credit plays a vital role in regulating the export-import process due to the guarantee and insurance it provides for both vendors and purchasers according to their international contract sale, which actually contributes to a prosperous international commerce basing mainly upon speed and trust. As any other contract- biding for both parties, the documentary credit requires the two parties with some commitments (the bank opening the credit and the client). However, the contract in its very nature ,requires -in the execution step- the bank to assume other commitments for the client benefitting of the credit. As the bank deemed as the pivotal point around which the process turns, we tried through this very study discuss in details the conditions to fulfill with the documentary credit by both vendors and purchasers and as well shed light on the legal responsibility arising from violating any of the related commitments.
Keywords: الاعتماد المستندي ; البنك فاتح الاعتماد ; العميل الآمر ; البائع المستفيد; Documentary credit- the bank opening the credit- the client-the beneficiary vendor.